Selling loyalty and its Relationship to Legitimate Intentions - an Analytical Study- - Ali , Mikayiyl (Islamic Sciences Journal, 2023)
ABSTRACT Fulfillment sale is one among the contemporary contracts that require a study and clarification in terms of the legal ruling for these sorts of contracts, because of its spread among people, and to satisfy their needs, because it is a reasonable contract for both parties, and therefore the interest is achieved for them. Therefore, the principle within the sale must be binding and final, without rescission, if the contract is valid with its pillars, conditions and place, because it will have its legal effects since it results in the transfer of the ownership of the thing sold to the customer fully. As for a fulfillment sale, it is an accept which the vendor keeps for himself and has the proper to recover the sold item during a particular period reciprocally for refunding the first price and therefore the expenses incurred within the sale, and therefore the expenses of necessary or beneficial repairs apart from luxury. This contract has spread among the people as an alternate to usurious loans, whereby the vendor gets the cash without abandoning his money through the definitive sale, and therefore the buyer benefits from his money surplus to his needs without falling into usury through the utilization of the sale in fulfillment. Therefore, the need for the study of jurisprudence and in a comprehensive way was necessary, for the position of the tolerant Islamic law of it. The fulfillment sale aims to realize a double goal represented in documenting the debt that the vendor paid, so it is considered because the legitimate answer for the two parties to the contract and does not transfer the ownership of the sale to the customer, but rather owns the benefit, and thus it is one among the contracts of in-kind guarantee like a mortgage.